Does ecology has an impact on seed dormancy??? - Sanghamitra, P; Sahu, R K; Singh, Lalan Kumar; Moharana, Debashis; Bagchi, T B; Munda, Sushmita; Sarkar, Sutapa; Basak, Nabaneeta; Kumar, Gaurav; Yadav, Manoj Kumar; Bose, L K; Marandi, B C; et al. (ORYZA-An International Journal of Rice, 2018)
About 91 varieties of different ecology released from National Rice Research Institute(NRRI),Cuttack were screened for duration of seed  dormancy harvested after 25,30 and 35 days of heading. The varieties harvested after 25 days of heading showed 0-37 days of dormancy with Lunishree was observed as strongly dormant with 37days of dormancy duration. Moderate dormancy(≥20days) was observed in Jayanti, Kamesh, Jayantidhan,Nua chinikamini, Nua kalajeera, and Luni shree harvested at 30days after heading. The varieties that were collected after 35 days of heading showed 0-20 days of dormancy and were mostly non dormant and weakly dormant at this stage of sampling. Varieties Jayanti, Nua chinikamini, and Lunishree identified with  moderate seed dormancy(≥15 days)  may  be useful for breeding programme. Highest duration of dormancy was observed in the varieties developed for coastal salinity followed by deep water ecology. Variation in duration of dormancy of the variety Luna Sampad  grown in two different ecologies strengthen the  influence of ecology on seed dormancy.